Experimental investigation and mathematical modelling of thermal performance characteristics of textiles incorporating phase change materials (PCMs) - Jaworski, Maciej; Wnuk, Ryszard; Cieślak, Małgorzata; Goetzendorf-Grabowska, Bogna (International Conference “Environmental Engineering”, 2017)
Impregnation of textiles (fabrics) by phase change materials (PCMs) changes their thermal properties. High thermal capacity of PCMs, due to large enthalpy of phase change (latent heat), increases the potential of these materials for heat accumulation, but also modifies heat transfer in transient states what improves their insulating characteristics. The paper presents selected results of both experimental and theoretical investigation of the thermal behavior of textiles impregnated with phase change materials, PCMs, under variable thermal loads. Thermal capacity of textiles containing different amounts of microencapsulated PCM were measured with DSC. Then, their thermal behavior characteristics were investigated under irradiation from a solar simulator (heating phase) and during cooling in the regime of natural convection. Mathematical model of heat transfer in the textiles, including radiative and convective boundary conditions, was formulated. Computer simulations of the processes under study, validated on the base of experimental results, allowed to determine important properties of the textiles, such as coefficients of absorption and transmission for solar radiation. Overall thermal characteristics of the textiles, i.e. temperature variations under different thermal loads, are also presented in the paper.